Putting Oils to Avoid Friction: An Islamic Microfinance Aid for Cafepreneurs - Muhammad Zuki, Mohd Faizuddin; Abdul Rahim, Razinda Tasnim; Redzuan, Nur Harena; Rosman, Romzie; Shaharuddin, Siti Saffa (Universiti Utara Malaysia 06010 UUM Sintok, Kedah MALAYSIA, 2024)
This case study presents the entrepreneurial journey of Syafiq, the owner of Kupikir Cafe in Jitra, Kedah. At 34 years old, with a Diploma in Hotel and Catering Management and five years in the F&B industry, Syafiq leverages Islamic microfinance to establish and grow his business. This financial aid, compliant with Shariah principles, provided crucial support for renovations, quality improvements, and digital transformations, such as marketing through Instagram and partnering with Grab Food for deliveries. Despite these successes, Syafiq faces challenges like inconsistent income, rising material costs, and managing employee behaviour. His contemplation of reapplying for the microfinance facility is influenced by both the positive impacts and the ethical alignment with his Islamic faith, despite the appeal of lower rates from conventional microfinance options. Additionally, Syafiq plans an early exit strategy, seeking a balance between business and family life. As he navigates this moment of inertia, the pivotal question remains: Does borrowing again matter? This decision will shape the future of Kupikir Cafe and Syafiq s personal aspirations, highlighting the complex interplay between entrepreneurship, ethics, and strategic planning.